Antifungal Thiazolidines: Synthesis and Biological Evaluation of Mycosidine Congeners - Levshin, Igor B.; Simonov, Alexander Y.; Lavrenov, Sergey N.; Panov, Alexey A.; Grammatikova, Natalia E.; Alexandrov, Alexander A.; Ghazy, Eslam S. M. O.; Savin, Nikita A.; Gorelkin, Peter V.; Erofeev, Alexander S.; Polshakov, Vladimir I. (Pharmaceuticals (Basel, Switzerland), 2022)
Novel derivatives of Mycosidine (3,5-substituted thiazolidine-2,4-diones) are synthesized by Knoevenagel condensation and reactions of thiazolidines with chloroformates or halo-acetic acid esters. Furthermore, 5-Arylidene-2,4-thiazolidinediones and their 2-thioxo analogs containing halogen and hydroxy groups or di(benzyloxy) substituents in 5-benzylidene moiety are tested for antifungal activity in vitro. Some of the synthesized compounds exhibit high antifungal activity, both fungistatic and fungicidal, and lead to morphological changes in the Candida yeast cell wall. Based on the use of limited proteomic screening and toxicity analysis in mutants, we show that Mycosidine activity is associated with glucose transport. This suggests that this first-in-class antifungal drug has a novel mechanism of action that deserves further study.